Peril at the exposition - March, Nev, 1967- (March, Nev, 1967- Captain Jim and Lady Diana mysteries., 2022)
"Captain Jim Agnihotri and his new bride, Diana Framji, return in Nev March's Peril at the Exposition, the follow up to March's award-winning, Edgar finalist debut, Murder in Old Bombay. 1893: Newlyweds Captain Jim Agnihotri and Diana Framji are settling into their new home in Boston, Massachusetts, having fled the strict social rules of British-ruled Bombay. It's a different life than what they left behind, but theirs is no ordinary marriage: Jim, now a detective at the Dupree Agency, is teaching Diana the art of deduction he's learned from his idol, Sherlock Holmes. Everyone is talking about the preparations for the World's Fair in Chicago: the grandeur, the speculation, the trickery. And Jim will experience it first-hand: he's being sent to Chicago to investigate the murder of a man named Thomas Grewe. As Jim probes the underbelly of Chicago's docks, warehouses, and taverns, he discovers deep social unrest and some deadly ambitions. When Jim goes missing, Diana must venture to Chicago's treacherous streets to learn what happened, and prevent disaster. Readers can be sure that another exciting adventure is at hand for Lady Diana and Captain Jim. Award-winning author Nev March mesmerized readers with her debut novel, Murder in Old Bombay. Now, in Peril at the Exposition, she wields her craft against the glittering landscape of the Gilded Age with spectacular results"--